SUCCESS FACTORS OF LEAN MANAGEMENT IMPLEMENTATION IN PUBLIC SERVICE ORGANIZATIONS (Journal of Technology and Operations Management, 2016)
Lean management is a management approach adapted from the lean manufacturing concept which focuses on waste elimination and continuous improvement. While the manufacturing sector has widely implemented lean in their operation, the application of lean in the service sector is still new. Public service organizations chose to apply lean management in order to cope with the need to improve performance while reducing costs. However, most transformational efforts failed because of public organizations did not focus on the right element. The objective of this study is to investigate the success factor of lean implementation in public service organizations. The interview was conducted at five public organizations that have received recognition of excellence practices in lean management by Malaysia Productivity Corporation. The data were analyzed using Atlas.ti software. From the analysis, seven success factors have been identified which are; management commitment, communication, employee involvement, culture, knowledge, teamwork and organization readiness. The factors mentioned should be incorporated in the change program and should be well managed by the management of public service organizations to gain success and ensure sustainability of lean management implementation.